A successful introduction to a non-expert setting of the thin-layer agar Colour Test as an indirect phenotypic drug susceptibility test for Mycobacterium tuberculosis. (March 2021) - Klaos, Kadri; Agejeva, Anna; Kummik, Tiina; Laks, Sirje; Remets, Olesja; Sasi, Sirje; Tann, Anneli; Viiklepp, Piret; Altraja, Alan
Highlights: Results from the thin-layer agar MDR/XDR-TB Colour Test are highly reproducible. Implementation of the thin-layer agar Colour Test does not require skilled personnel. Reading of the Colour Test indirect drug susceptibility test (DST) by inexperienced technicians is accurate. The M. tuberculosis Colour Test DST in raw settings is consistent with MGIT 960 DST. Abstract: Objectives: We evaluated the performance of the MDR/XDR-TB Colour Test (CT) as an in-house thin-layer agar-based indirect drug susceptibility test (DST) for Mycobacterium tuberculosis (MTB) in a non-expert setting in Estonia. Methods: After 2 days of hands-on training for laboratory technicians, 6 panels of 150 MTB isolates were cultured onto CT plates prepared in-house in 2 laboratories. Triplicate readings of 900 CT plates resulted in 18 DST patterns for each initial isolate. Time intervals to the results and for media preparation were estimated, and intra- and interobserver agreement, test sensitivities and specificities were calculated. BACTEC MGIT 960 DST was used as a reference. Results: The median time to produce DST results for isoniazid, rifampicin and levofloxacin was 13 days. CT sensitivity was 94.7% for levofloxacin, 95.8% for isoniazid and 97.3% for rifampicin. Test specificities were >97% for all 3 drugs. Interobserver agreement was 100% in Lab A and in Lab B >97% for levofloxacin and 99% for isoniazid and rifampicin. Conclusions: The implementation of the CT into a new laboratory was straightforward with only minimal guidance required. This study proves that the CT is highly reproducible and easily interpreted by previously inexperienced personnel.